2011
DOI: 10.1007/s00360-011-0549-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of aging among healthy, older bottlenose dolphins (Tursiops truncatus): comparisons with aging humans

Abstract: Changes in hematological and serum chemistry values have been identified among older compared to younger humans. We hypothesized that healthy bottlenose dolphins (Tursiops truncatus) 30 years and older may demonstrate similar clinicopathological changes with increasing age. Retrospective hematological and serum chemistry data generated from routine, fasted blood samples collected over 10 to 20 years among six healthy dolphins that lived at least 40 years were analyzed to (1) assess linear trends in blood varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 90 publications
2
50
1
Order By: Relevance
“…This result would support data from previous studies in which no obvious changes were detected in hepatic tissue during the process of ageing (Schmucker et al, 1984;Kitani, 1991;Venn-Watson et al, 2011).…”
Section: Liversupporting
confidence: 94%
“…This result would support data from previous studies in which no obvious changes were detected in hepatic tissue during the process of ageing (Schmucker et al, 1984;Kitani, 1991;Venn-Watson et al, 2011).…”
Section: Liversupporting
confidence: 94%
“…Mean basal insulin in this group was ∼12 μIU/ml but mean insulin 2 h-post-prandial was lower (∼9 μIU/ml) (1). These data are difficult to interpret because insulin levels in this small group showed substantial variability, particularly the post-prandial measurements, possibly due to influences of gender and age, as noted for other hematologic and biochemical parameters (103). Further study with larger groups and uniform populations is needed to place these initial findings into context.…”
Section: “Diabetes Pathology” In Normal Carnivoresmentioning
confidence: 80%
“…In three separate studies, fasting glucose in captive bottlenose dolphins was determined to be between 108 and 194 mg/dL (1, 2, 103). The largest study measured serum glucose in 1161 samples from 52 captive bottlenose dolphins and reported mean serum glucose concentrations of 108 and 112 mg/dL in fed and fasted conditions, respectively (2).…”
Section: Impact Of Domestication and Captivity On Carnivore Carbohydrmentioning
confidence: 99%
“…Several dolphin diseases have similar human counterparts, including type 2 diabetes [8], urate nephrolithiasis with renal failure [33], and iron overload with liver disease [9,34]. The dolphin may serve as a human model for several disease processes, as was recently proposed for type 2 diabetes [10] and aging studies [35], where new treatment modalities using stem cells could be realized.…”
Section: Discussionmentioning
confidence: 99%